Hermeneutical Analysis of the Concept of Makkiyah–Madaniyah in Mafhūm al-Naṣṣ by Nasr Hamid Abu Zayd - Muhammad Fadhil Hadziq; Muhammad Aqil Abror; Bulqis Bulqis; Sri Jomila Oktari; M. Fauzan Zenrif (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2026)
This study examines the classification of Makkiyah and Madaniyah in ʿUlūm al-Qur’ān with a focus on Nasr Hamid Abu Zayd’s hermeneutical critique of the classical approach, which tends to be descriptive and narration-centered. The research is important because it reveals epistemological problems in determining Makki–Madani classifications that affect the understanding of the Qur’anic text, the history of revelation, and the relationship between text and law. The method used is library research employing content analysis with a critical-hermeneutical approach to Mafhūm al-Naṣṣ and other classical and contemporary exegetical literature. The findings show that Makki–Madani criteria such as geography, audience, content, and narrations are not absolute and instead represent problematic historical constructions. Abu Zayd also critiques the method of talfīq al-riwāyāt, the assumption of ta‘addud al-nuzūl, and the separation between text and law, all of which contribute to an epistemological crisis in textual understanding. In addition, Qur’anic stylistic features are interpreted as historical indicators reflecting the socio-cultural dynamics of revelation. The study concludes that Makki–Madani should be understood in a historical-contextual and hermeneutical framework as a dynamic process involving text, reality, and interpretation. These findings are significant because they offer a methodological reconstruction in Qur’anic studies that is more critical, integrative, and contextual. This research is expected to contribute to contemporary Qur’anic studies by emphasizing a critical, historical, and dialogical approach to understanding revelation more comprehensively and relevantly for scholarly discourse.